1989
DOI: 10.1016/0169-4758(89)90298-6
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Trichomoniasis

Abstract: Although virtually unknown in Europe since the widespread adoption of artificial insemination (AI), infection by the sexually transmitted protozoan parasite Tritrichomonas foetus (Fig. 1) results in substantial economic losses throughout the major cattle-rearing areas of the world where natural breeding is relied upon. Infection by T. foetus is increasingly recognized as a significant cause of bovine infertility. In this review, Alex Yule, Susan Skirrow and Robert BonDurant summarize the current knowledge of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…With reference to trichomonads, it has been suggested that they play roles as virulence factors (5,6,26,27,34,46) and as adherence factors (2,13,31), and it has been suggested that CPs contribute to pathogenesis when released into the host mucosal surface (8,45,48). A role in evasion of the host immune response (14,20,32,37) has also been suggested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to trichomonads, it has been suggested that they play roles as virulence factors (5,6,26,27,34,46) and as adherence factors (2,13,31), and it has been suggested that CPs contribute to pathogenesis when released into the host mucosal surface (8,45,48). A role in evasion of the host immune response (14,20,32,37) has also been suggested.…”
mentioning
confidence: 99%
“…Bovine trichomoniasis causes considerable economic loss in the United States, Canada, and South America, as well as in other parts of the world where open range management and natural breeding are practiced (3,8,10,11,15,48). The disease is characterized by chronic genital tract infection with inflammation and reproductive failure (3,11,15).…”
mentioning
confidence: 99%
“…In bulls the parasite can be found from the preputial cavity until urethra, and also in deeper parts of the animal's urogenital tract. The parasite is usually found harbored in the animal's preputial cavity, and once infected bulls may harbor T. foetus throughout their lives (Yule et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The human urogenital trichomoniasis is one of the most frequent non-viral worldwide sexual transmitted disease (STD) (Lockhart et al 1996, World Health Organization, 1995 affecting around 180 million people (Cotch et al 1991, Rein et al 1990 while T. foetus is the main cause of weight loss and abortion in cattle (Yule et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Bulls are asymptomatic chronic carriers and can infect cows during insemination, while cows are usually able to clear the infection within a few months. 13,16 The organisms are found primarily in the superficial layers of the preputial mucosa in bulls. 12 Preputial wash specimens for bulls and cervicovaginal mucus for cows are the desired samples for diagnosis of trichomoniasis.…”
mentioning
confidence: 99%